Two new species of Cytospora (Diaporthales, Cytosporaceae) causing canker disease of Malus domestica and M. sieversii in Xinjiang, China - Guifang Cai; Ying Zhao; Yawei Zhai; Meilin Yan; Rong Ma; Daoyuan Zhang (MycoKeys)
Apple tree canker is a serious disease caused by species of Cytospora. Xinjiang Uygur Autonomous Region is one of the most important apple-producing areas in China. However, losses due to apple Cytospora canker have seriously damaged the apple industry and affected the economic development of the apple growers in this region. In this study, we used morphological characteristics combined with multilocus phylogenetic analyses of the ITS, act, rpb2, tef1 and tub2 loci to identify isolates from apple (Malus domestica) and wild apple (M. sieversii). As a result, C. hippophaopsis sp. nov. from M. sieversii and C. shawanensis sp. nov. from M. domestica were discovered and proposed herein. Pathogenicity tests were further conducted on 13 varieties of apple and wild apple, which confirmed C. hippophaopsis and C. shawanensis as canker pathogens. Meanwhile, C. hippophaopsis is generally more aggressive than C. shawanensis on the tested varieties of apple and wild apple.